The epistemology of utopia : rhetoric, theory and imagination - Silva, Jorge Miguel Bastos da, 1971- (Cambridge Scholars Pub., 2013)
The emergence of Utopian Studies as a dynamic field of inquiry situated at the crossroads of several disciplines is a striking development of the past few decades. It is symptomatic of a general trend towards the overcoming of epistemological and institutional boundaries, and has borne fruit in a number of ways. The traditions of utopianism have come to be valued as an important nurturing of possibilities, devoted to the critique and the transformation of the world. By undertaking the critica ...